Impact of Self-Monitoring Blood Glucose on Glycaemic Control Among Insulin-Treated Patients With Diabetes Mellitus in Northeastern Tanzania: A Randomised Controlled Trial - Sophia S. Muhali; Fatma S. Muhali; Sayoki G. Mfinanga; Abid M. Sadiq; Annette A. Marandu; Norman J. Kyala; Fuad H. Said; Eliada B. Nziku; Tumaini E. Mirai; James S. Ngocho; Henry L. Mlay; Gilbert G. Waria; et al. (Journal of Diabetes Research)
Trial Registration: Pan African Clinical Trials Registry identifier: PACTR202402642155729.